Low willingness to vaccinate against herpes zoster in a Chinese metropolis. Issue 11 (2nd November 2021) - Lu, Xinyue; Lu, Jia; Zhang, Felicia; Wagner, Abram L.; Zhang, Liping; Mei, Kewen; Guan, Baichu; Lu, Yihan
ABSTRACT: Background: Herpes zoster vaccine (HZV) has been available in China's mainland since June 2020. This study estimated willingness to receive HZV to characterize factors that may influence vaccination willingness. Methods: We conducted a face-to-face questionnaire survey in adults aged 50–69 years in 13 communities in Shanghai in late 2020. We explored the relationship between vaccination willingness and independent factors including demographic factors, medical history, knowledge of herpes zoster and HZV, and vaccine hesitancy. Outcomes included participants' willingness to vaccinate themselves, their partners, and their parents, under both the current payment scenario (self-payment) and a hypothetical scenario (payment by basic medical insurance). Results: A total of 1672 respondents aged 50–69 years were included in this study. The proportion of respondents willing to get vaccinated was 16.57% for themselves, 13.88% for their partners, and 8.49% for their parents. If the vaccine was covered under insurance, these numbers increased to 72.25%, 62.50%, and 29.96%, respectively. Younger age, female gender, higher income, higher educational level, local residents, and lower vaccine hesitancy were associated with increased willingness to vaccinate. Knowledge of herpes zoster and HZV positively influenced the willingness in the hypothetical payment scenario. Conclusion: We determined a very low willingness to vaccinate HZV in adults aged 50–69 years in a Chinese metropolis. Decreasing costs is important to increase coverage. Additionally, strengthening advocacy and health promotion for the vaccine will be particularly important, especially for groups with certain underlying diseases.